Productivity Improvement Through Line Balancing at Electronic Company - Case Study - A. F. H., Fansuri; A. N. M., Rose; M. F. F., Ab. Rashid; N. M. Zuki, N. M.; H., Ahmad (IOP Publishing, 2018)
A good manufacturing practice for production assembly can result in better productivity for the organization. This study focusses on productivity improvement of Electronics Manufacturing Service Company (EMSC) production assembly. It also aims to reduce waste and to propose a leaner line balancing with the elimination of non-value-added activities during the assembly. This study also aims to utilize current workstation to carter for the needs of the workstation to achieve 39 seconds takt time. Time study has been conducted for all workstations and found that all of the cycle time for each workstation exceeds the required takt time of 39 seconds. The bottleneck is at workstation number two with a recorded standard time of 54.1 seconds to complete the assembly thus causes high work in progress at workstation number two and excessive operator idle time to subsequent workstations. The main issue of EMSC is high volume demands from the customer and committing to the shipment plan. By adding one additional operator to workstation number two and a proper distribution of tasks may help EMSC to increase their production output. Time study is recorded in standard work form for future improvement.